Lecturer's Efforts to Improve Student's Digital Literacy through Online Learning - Ulya, Vita Fitriatul; Fitri, Nur Lailatul (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2024)
Nowadays, as digital consumers in the adolescent and early adult demographic, students tend to prefer search engines over printed books when seeking information. This shift reflects changing preferences in information access, with the internet and search engines like Google becoming the primary sources of knowledge for the current generation. However, even though students tend to rely on search engines, they must develop a profound digital literacy level. This study aims to determine the efforts of lecturers in the Tarbiyah Faculty of IAI Al-Hikmah Tuban to strengthen students' digital literacy through online learning. This research approach is quantitative. The data obtained from the results of questionnaires to lecturers as respondents are then described, and conclusions drawn. The results obtained from this study are that all lecturers are still consistently implementing online learning and are considered quite effective in strengthening student digital literacy. Efforts by lecturers to improve students' digital literacy include activities such as assigning tasks, reinforcing lecture materials, and replacing class hours with sessions conducted via Google Classroom, Google Meet, Zoom Meeting, and WhatsApp. No significant obstacles are experienced by lecturers and students of the Tarbiyah Faculty of IAI Al-Hikmah Tuban operating the online learning platform. It's just that sometimes they are constrained by the internet network and cottage students who cannot independently access online learning applications due to limited computer technology facilities. This research demonstrates the importance of student's ability to operate technology in learning and highlights the role of lecturers in the success of students' digital literacy in the future.